Social Norms and Self-Management Ability among Uninsured Primary Care Patients. Issue 8 (August 2020) - Kamimura, Akiko; Higham, Rebecca; Panahi, Samin; Lee, Edward; Ashby, Jeanie
Abstract : Objectives: The purpose of this study was to examine the association between social norms and self-management ability among uninsured low-income primary care patients. Methods: Data were collected from adult patients at a free clinic using a self-administered survey from August to December 2018. Results: Higher levels of social norms to exercise were associated with higher levels of all aspects of self-management ability. Lower levels of social norms to use substances were associated with higher levels of all aspects of self-management ability, except for variety in self-management. Better health was associated with higher levels of investment behavior of self-management ability. Conclusions: The findings of this study suggest the association between social norms and self-management ability and its impact on health among low-income, uninsured primary care patients. Self-management ability is important for maintaining health. Providing intervention programs on self-management skills should focus on not only individual behaviors but also social norms that affect their health behaviors. Abstract : Self-management of chronic conditions is important to improve health outcomes. Low-income patients often experience challenges in self-management for chronic conditions, however. This study provides an overview of the association between social norms and self-management ability among low-income primary care patients.